2016
DOI: 10.1111/asj.12496
|View full text |Cite
|
Sign up to set email alerts
|

Changes of microbial spoilage, lipid-protein oxidation and physicochemical properties during post mortem refrigerated storage of goat meat

Abstract: Examined was the effect of post mortem refrigerated storage on microbial spoilage, lipid-protein oxidation and physicochemical traits of goat meat. Seven Boer bucks were slaughtered, eviscerated and aged for 24 h. The Longissimus lumborum (LL) and Semitendinosus (ST) muscles were excised and subjected to 13 days post mortem refrigerated storage. The pH, lipid and protein oxidation, tenderness, color and drip loss were determined in LL while microbiological analysis was performed on ST. Bacterial counts general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
30
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 80 publications
10
30
2
1
Order By: Relevance
“…The decrease in the free thiol content and the increase in carbonyl content over storage are consistent with the findings of Lund et al (2008). Similarly, Sabow et al (2016) observed that the concentration of free thiol decreased during a 14 day chill storage of chevon.…”
Section: Antioxidant Statussupporting
confidence: 86%
See 2 more Smart Citations
“…The decrease in the free thiol content and the increase in carbonyl content over storage are consistent with the findings of Lund et al (2008). Similarly, Sabow et al (2016) observed that the concentration of free thiol decreased during a 14 day chill storage of chevon.…”
Section: Antioxidant Statussupporting
confidence: 86%
“…This observation could be due to the degradation of myofibrillar proteins in the course of ageing. Similar findings were found in chevon (Sabow et al 2016) and beef (Marino et al 2013). During post mortem, the accumulation of Ca 2+ into the muscle sarcoplasm leads to the activation of μ-calpain which in turn destabilizes the intact myofibrillar structure by degrading myofibrillar proteins involving titin, filamin, troponin-T and desmi (Lomiwes et al 2014).…”
Section: Physicochemical Properties and Chemical Compositionsupporting
confidence: 73%
See 1 more Smart Citation
“…Zakrys et al (2008) showed that instrumental a* value had a negative correlation, while L* value had a positive correlation with post mortem storage days. This suggests that samples became less red and lighter over the duration of storage (Sabow et al, 2016). The increase in L* value as storage progressed is in line with the report of Sabow et al (2015b), who observed that ageing improved lightness of chevon.…”
Section: Resultssupporting
confidence: 90%
“…Redness is the most significant colour parameter for assessing meat oxidation Sabow et al, 2016). Zakrys et al (2008) showed that instrumental a* value had a negative correlation, while L* value had a positive correlation with post mortem storage days.…”
Section: Resultsmentioning
confidence: 98%